O uso de Big Data como ferramenta de governança pública com foco nos impactos na sociedade, cultura, poder e relações de trabalho no governo de Mato Grosso - Ferraz, Paulo Francisco Munhoz (2024)
This dissertation addresses the social transformations resulting from technological development in globalization, highlighting the importance and impact of this development in the construction of identities and subjectivities in contemporary societies. It also demonstrates the advantages of using Big Data as a technology and the challenges arising from its large-scale use, with the main objective of analyzing the impacts of Big Data as a governance tool in the context of the government of Mato Grosso in 2024. The methodological approach is hybrid, with qualitative and quantitative resources and techniques. It begins with an exploratory phase to deepen the theoretical basis and collect data, using bibliographic research and applying a questionnaire, concomitantly, with the descriptive route. The investigation presents reflections on the construction of citizen profiles based on these data, involving ethical and social issues that need to be debated. The methodology was based on some themes such as consumer society, globalization, use of Big Data and conducted research with public servants in the State of Mato Grosso, on the use of Big Data as an ecosystem implemented in public bodies. The results indicated that, although the application of Big Data is perceived as an effective tool for optimizing public services and increasing transparency, significant challenges remain, including concerns about privacy, the centralization of power, and inequality of access. The research revealed mixed perceptions among public servants, highlighting the need for greater training, more effective regulations, and improvements in technological infrastructure. It is concluded that the use of Big Data in the government of Mato Grosso has transformative potential but requires an ethical and inclusive approach to mitigate risks and ensure equitable benefits for society, while respecting citizens' privacy and strengthening public governance.